(untitled) (Patrimônio e Memória, 2017)
This paper aims to analyze “Regresso à cúpula da Pena”, a short story by José Rodrigues Miguéis described by Eduardo Lourenço as “the most revealing and deep text raised by the experience of exile” in the Portuguese literature. Insofar as the association between literature and exile has already been discussed by prominent authors, we introduce our approach to the text by using the reflections proposed by Bolaño, Cortázar and Said. Then we proceed to a close reading of the narrative with the purpose of showing its organization similar to a novella, marked by the succession of events in an ascending rhythm that leads to an outcome already qualified as implausible by the critic. In turn, we defend that the narrative, by exploring the boundaries between dream and reality, leads to the unlikely conclusion as a strategy of ironic representation of the contrast between the dreamed return and the return indeed experienced by the protagonist.